Exploring the Relationship Between Inflation and Income Inequality: Evidence from Emerging Markets (Universitas Kristen Indonesia Toraja, 2023)
This paper examines the complex relationship between inflation and income inequality in emerging markets. Using panel data analysis, the study identifies the channels through which inflation exacerbates or mitigates income disparities. The paper provides policy recommendations for balancing monetary stability and equitable income distribution, drawing on evidence from Latin America, Asia, and Africa.